Isolation methodology is essential to the evaluation of the extracellular vesicle component of the senescence‐associated secretory phenotype - Ryan Wallis (Journal of Extracellular Vesicles, 2021)
Abstract A hallmark of senescence is the acquisition of an enhanced secretome comprising inflammatory mediators and tissue remodelling agents – the senescence‐associated secretory phenotype (SASP). Through the SASP, senescent cells are hypothesised to contribute to both ageing and pathologies associated with age. Whilst soluble factors have been the most widely investigated components of the SASP, there is growing evidence that small extracellular vesicles (EVs) comprise functionally important constituents. Thus, dissecting the contribution of the soluble SASP from the vesicular component is crucial to elucidating the functional significance of senescent cell derived EVs. Here, we take advantage of a systematic proteomics based approach to determine that soluble SASP factors co‐isolate with EVs following differential ultracentrifugation (dUC). We present size‐exclusion chromatography (SEC) as a method for separation of the soluble and vesicular components of the senescent secretome and thus EV purification. Furthermore, we demonstrate that SEC EVs isolated from senescent cells contribute to non‐cell autonomous paracrine senescence. Therefore, this work emphasises the requirement for methodological rigor due to the propensity of SASP components to co‐isolate during dUC and provides a framework for future investigations of the vesicular component of the SASP.